2017
DOI: 10.1016/j.ijimpeng.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearity of interfaces and force transmission of bolted flange joints under impact loading

Abstract: Vibration of flange joints and force transmission characteristics of connection interfaces are important due to concerns over the structural strength and signal identification in engineering structures such as missiles and rockets. However, nonlinear factors such as clearance, damping and discontinuous interfaces make it difficult to predict the responses under specific excitations such as shock impacts. This paper proposed a typical configuration of a bolted flange joint and investigated the response of vibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Prinz et al carried out horizontal quasistatic loading experiments on bolted beam-column structures, the numerical simulation model is established according to this structure, and a reasonably accurate of the finite element model with shell elements and nonlinear springs for the loading response is verified [10]. Guo et al proposed a typical configuration of the bolted flange joint and investigated the response of vibration and dissipation of the joint under a series of impact loading with the simulation model, validated by a revised SHPB (Split Hopkinson pressure bar) experiment [11]. Consequently, the researcher's attention has been attracted in the experimental study on the typical bolted connection structure, and more failure experiment under different and complicated loading condition corresponding to different application background of these structures should be designed and implemented as a reference for the engineering application.…”
Section: Introductionmentioning
confidence: 95%
“…Prinz et al carried out horizontal quasistatic loading experiments on bolted beam-column structures, the numerical simulation model is established according to this structure, and a reasonably accurate of the finite element model with shell elements and nonlinear springs for the loading response is verified [10]. Guo et al proposed a typical configuration of the bolted flange joint and investigated the response of vibration and dissipation of the joint under a series of impact loading with the simulation model, validated by a revised SHPB (Split Hopkinson pressure bar) experiment [11]. Consequently, the researcher's attention has been attracted in the experimental study on the typical bolted connection structure, and more failure experiment under different and complicated loading condition corresponding to different application background of these structures should be designed and implemented as a reference for the engineering application.…”
Section: Introductionmentioning
confidence: 95%
“…According to Eurocode 3 (BS EN 1993-1-8:2005), 28 the translational stiffness of joints with more than two columns of preloaded bolts can be taken as an infinitely large number. In the FE model, the stiffness of each spring k 1 , k 2 , k 4 and k 5 is assumed to be 1310 10 N=m. Six accelerometers are used in this study to measure the dynamic behaviour of the steel frame when the steel frame is excited with an impulse hammer.…”
Section: Numerical Modelling Of Connection Stiffnessesmentioning
confidence: 99%
“…Discontinuous interfaces at the bolted connections region introduce structural damping and nonlinear contact. 10 Micro- and meso-scale parameters like geometry, roughness and bolt preload govern the contact nonlinearity, 11 and it is computationally very expensive to include those effects in a macro-scale model. The study by Hammami et al 12 concluded that the level of junction coupling has sufficient influence on the dynamic system to induce damping.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the wavelet analysis, the frequency components of the structural response of the projectile-fuze system were explored. Guo et al [7] studied the force transmission process based on the revised SHPB (Split Hopkinson pressure bar) and proposed that the structural response of composite structure consisted of three terms, namely, structural vibration, forced vibration, and shock response. In the abovementioned research, the rigid-body deceleration is considered as the input condition to investigate the structural response of the system.…”
Section: Introductionmentioning
confidence: 99%